Creating the cultures of the future: cultural strategy, policy and institutions in Gramsci. Part three: Is there a theory of cultural policy in Gramsci’s prison notebooks? - Merli, Paola (Taylor & Francis, 2013)
In this article, I argue that Gramsci’s prison notes on questions of cultural strategy, policy and institutions, which have so far been largely overlooked by scholars, provide further analytical insights to those offered by his more general concepts. Together they enrich the theoretical underpinnings for critical frameworks of analysis as well as for radical practices of cultural strategy, cultural policy-making and cultural organisation. On the basis of a detailed analysis of these notes, I then answer the question of whether they amount to a theory of cultural policy.